Performance of stochastic Runge-Kutta Methods in approximating the solution of stochastic model in biological system - Noor Amalina Nisa, Ariffin; Norhayati, Rosli; Mazma Syahidatul Ayuni, Mazlan; Adam, Samsudin (IOP Publishing, 2017)
Recently, modelling the biological systems by using stochastic differential equations (SDEs) are becoming an interest among researchers. In SDEs the random fluctuations are taking into account, which resulting to the complexity of finding the exact solution of SDEs and contribute to the increasing number of research focusing in finding the best numerical approach to solve the systems of SDEs. This paper will examine the performance of 4-stage stochastic Runge-Kutta (SRK4) and specific stochastic Runge-Kutta (SRKS) methods with order 1.5 in approximating the solution of stochastic model in biological system. A comparative study of SRK4 and SRKS method will be presented in this paper. The non-linear biological model will be used to examine the performance of both methods and the result of numerical experiment will be discussed.